State-Business Relations and Electric Vehicle Industrial Policy in ASEAN: Evidence from Indonesia, Thailand, and Vietnam - Aswin Ariyanto Azis; Bintang Corvi Diphda (Universitas Cenderawasih, 2026)
This article examines how political economy factors, particularly state-business relations and political context that shape electric vehicle (EV) industrial policy in ASEAN. Using a comparative political economy approach, it analyzes Indonesia, Thailand, and Vietnam through four dimensions: policy process, state motivations, capability formation, and enforcement of government support. The study finds that variations in coordination mechanisms and bargaining structures between governments and firms explain divergent policy mixes and industrial upgrading trajectories despite similar policy goals. Thailand demonstrates institutionalized coordination with enforceable conditionality that supports supplier upgrading; Indonesia adopts executive-led downstreaming with state-owned enterprise brokerage and evolving local content requirements; while Vietnam employs a decree-driven, champion-led model focused on scaling production but with limited supplier inclusion. The article contributes to the literature by showing that effective industrial upgrading depends on where coordination authority is located and how credible and enforceable policy conditionality is, rather than on incentives alone. KEYWORDSASEAN; Electric Vehicle; Industrial Policy.